PAMONG'S INTERPERSONAL COMMUNICATION STRATEGY IN FOSTERING THE PERSONALITY OF TERRORISM INMATES IN GUNUNG SINDUR SPECIAL PRISON - Aji, Trio Saputro; Simanjuntak, Meitisa Vanya (Universitas Nusa Cendana, 2025)
This research investigates the interpersonal communication strategies employed by prison officers (pamong) in fostering the personality development of terrorism inmates at Gunung Sindur Special Prison. The background of this study highlights the unique challenges faced in rehabilitating terrorism convicts, necessitating effective communication methods tailored to their specific needs. The primary objective is to identify and analyze these communication strategies to enhance the effectiveness of rehabilitation programs. Utilizing a qualitative research method, the study gathers data through direct observations and interviews with involved personnel, providing a comprehensive understanding of the communication dynamics at play. The results indicate that successful communication relies on building trust through simple messages before addressing sensitive topics. However, challenges such as the dual responsibilities of officers, lack of specialized training in psychology, and inadequate security resources hinder the overall effectiveness of the mentoring process. These findings emphasize the need for improved training and resource allocation to enhance rehabilitation efforts. Keywords: Interpersonal Communication; Terrorism Inmates; Rehabilitation Strategies